Changes in the start reaction times in the 200 m run at the World Championships after the tightening of false start rule - Mitasik, P.; Dolezajova, L.; Lednicky, A.; Vegh, D. (Acta Facultatis Educationis Physicae Universitatis Comenianae, 2020)
Reaction time is an important component of the structure of sports performance in sprint disciplines. In our observation, we focused on the men`s and women`s 200 metres discipline at the World Championships (WCH) in two periods. The first in 1999-2009 and the second in 2011-2019. This division was conditioned by the change in the false start rule, which states that any competitor who makes a false start, except in multicontest, will be disqualified (valid since 1st January 2010). This change affected the speed of the sprinter`s reaction. The monitored group were finalists of the 200 m runs at the WCH, a total of 11 events. We used basic mathematical-statistical characteristics and assessed changes in reaction times using parametric paired and parametric unpaired t-test and Wilcoxon test. We compared reaction time in the heats and the finals. We found that at some WCH, worse reaction times were achieved in the finals of both categories compared with the heats. By comparing the reaction speed in the heats with the reaction speed in the men`s finals, we recorded this statistically significant difference in the first period (p < 0.01) and after tightening the rule at the level of p < 0.10. In the women`s group, this difference was not statistically significant in any period. The percentage of the reaction speed in the final time of the 200 m run was 0.76 - 0.86 % in the men`s group and 0.74 - 0.78 % in the women`s group. The analysis of the results from the WCH in athletics confirmed the importance of reaction speed in the 200 m run.